Defense Against Criminal Theft Perpetrators Based on Islamic Law - Muhammad Abdi Manullang; Pagar Pagar; Ramadhan Syahmedi Siregar (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
This study aims to describe the legality of the defense of suspected perpetrators of criminal acts of theft carried out by LBH SIKAP based on Islamic law. This study is a field research (empirical study), using the results of observations and interviews with LBH SIKAP Advocates of Dairi Regency and the people of Dairi Regency as primary sources. Secondary sources include laws and regulations, including the Criminal Code (KUHP) and Law Number 16 of 2011 concerning Legal Aid. The results of the study: The practice of efforts to defend suspects in the crime of theft carried out by LBH SIKAP by way of direct assistance when the perpetrators are still at the investigation level; LBH SIKAP will provide assistance until the file is brought to the prosecutor's office so that the prosecution is carried out immediately, to assist the person who has the status of a defendant before the Panel of Judges of the Sidikalang District Court. The defense carried out by LBH SIKAP was carried out based on a request from the perpetrator or the perpetrator's family after an arrest by the police. LBH SIKAP advocates studied the files; then, the family approached the perpetrators to provide protection and assistance. The defense of suspected perpetrators of the crime of theft carried out by LBH SIKAP based on Islamic law is not prohibited. In general, the defense carried out by LBH SIKAP is part of professionalism and has been guaranteed by law.